Longitudinal analysis of axial length growth in a German cohort of healthy children and adolescents. (1st April 2021) - Truckenbrod, Carolin; Meigen, Christof; Brandt, Manuela; Vogel, Mandy; Sanz Diez, Pablo; Wahl, Siegfried; Jurkutat, Anne; Kiess, Wieland
Abstract: Purpose: To generate continuous growth curves for axial length (AL) in German children. We hypothesise that percentile curves of AL can be used as a predictive measure of myopia. Methods: In this longitudinal and cross‐sectional LIFE Child Study, children's non‐cycloplegic refraction data was collected using the Zeiss i.Profiler plus while AL was measured using the Haag‐Streit Lenstar. Reference growth curves were estimated as a continuous non‐parametric function of age. Results: Data from 4511 visits of 1965 participants (1021 boys and 944 girls) between 3 and 18 years of age were analysed. For all ages and percentiles, the estimated AL was higher in boys than girls. AL differences between boys and girls were most pronounced in the 98 th percentile at 3 years of age, being 0.93 mm longer eyes in boys. This difference decreased to 0.21 mm at 18 years of age. While the lower percentiles of AL reach their final value around age 13, the 50 th percentile was still increasing by 0.05 mm per year until the end of the observation period. While, in general, children with longer eyes are more likely to develop myopia, this relationship is weaker between the ages of 5 and 8. Conclusion: The LIFE Child Study data provides European AL data. In both Germany and China, AL has comparable growth rates when the baseline ALs are compared as percentiles. Thus, percentile curves of AL can be used as a predictive measure for the likelihood of developing as well as the progression of myopia.